Inhibition of Ethylene Production in Fruit Slices by a Rhizobitoxine Analog and Free Radical Scavengers - Baker, James E. (1978)
The rhizobitoxine analog, L-2-amino-4-(2-aminoethoxy)-trans-3-butenoic acid (Ro), which effectively inhibits ethylene production in apple (Malus domestica Borkh.) and other tissues at concentrations at about 68 micromolar, inhibited ethylene production by about 50 to 70% in green tomato (Lycopersicon esculentum Mill.) fruit slices but only by about 15% in pink and ripe tomato tissue slices. Ethylene production in climacteric-rise and postclimacteric avocado slices was likewise relatively insensitive to 68 micromolar Ro. At 340 micromolar Ro, inhibition of ethylene production increased up to 50% in pink tomato slices, whereas 680 micromolar Ro was required to inhibit ethylene production by 30% in avocado slices. Incorporation of (14)C from [(14)C]methionine into ethylene in green and pink tomato tissues was inhibited by Ro to about the same extent as inhibition of total ethylene production. Results thus far are inconclusive as to the mechanism of Ro resistance in tomato and avocado tissues. At 1 millimolar, free radical scavengers such as benzoate, propyl gallate, nordihydroguaiaretic acid, and to a lesser extent, eugenol, inhibited ethylene production in both Ro-sensitive (green tomato and apple) tissues and Ro-resistant (pink tomato and avocado) tissues. Therefore, free radical steps are suggested in the ethylene-forming systems.